Keeping medical science trustworthy: The threat by predatory journals - Olaf R. van Loon; A.J. (Tom) (Elsevier, 2023)
Since most scientific journals tend to ask article processes costs from authors, a new category of journals has developed of which the business model is commonly exclusively based on financial contributions by authors. Such journals have become known as predatory journals. The financial contributions that they ask are not always lower than those asked by high-quality journals although they offer less: there is commonly no real review, texts are not edited, and there are commonly no printed editions. The lack of serious reviews makes predatory journals attractive, however, particularly for authors of low-quality (or even fraudulent) manuscripts. It is shown here that numerous - commonly fairly recent - journals, some of which may predatory, attract manuscripts by approaching authors of articles in high-quality journals like Complementary Therapies in Medicine. Publication of articles in such journals contaminates thorough literature and undermines the trustworthiness of the medical society. Any involvement in such journals (as an author, reviewer or editor) of such journals should therefore be discouraged.